Aerobic fitness and isokinetic knee strength of semi-professional rugby union players: a comparison between backs and forwards - Baba, T.; Joyce, M.; Boibluche, S.; Hu, X.; McGrath, D.; Dubois, R.; Nicolas, G.; Prioux, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study aimed to describe the physical fitness characteristics of semi-professional rugby union (RU) players using VO2max (mL/min/kg), knee peak torque (PT), mean power (MP), hamstring: quadriceps (H:Q) ratio and basic anthropometrics characteristics and to compare backs and forwards across these same characteristics. METHODS: VO2max and ventilatory threshold (VT) as a percentage of VO2max were measured using the Bruce protocol maximal graded test. Knee strength test PT, MP and H:Q were analyzed using the isokinetic dynamometer test. Basic anthropometrics measures were obtained by measures of body mass, height (from Tanita Body Composition Analysis; Tanita Corp., Tokyo, Japan). While fat mass was measured using skinfold thicknesses taking from different body parts. Twenty-five semi-professional players aged (26.3±0.9 years) from the same team were recruited for the study. Mean experimental values from maximal graded test and isokinetic dynamometer test were analyzed using t-tests from the SigmaStat 3.11 program (Systat Software Inc., San Jose, CA, USA). RESULTS: The results showed that forwards were significant taller (P=0.036), heavier (P=0.01), with greater fat mass (P=0.001) than backs. Backs had a greater VO2max (P=0.02) than forwards. With forwards having a greater (P=0.01) eccentric H PT. CONCLUSIONS: This study presents important information for players and athletic coordinators as to the differences between backs and forwards across physiological and strength measures. This information can greatly inform the individualized training protocol and preparation of current and future players across different positions and different levels.